The Importance of Prayer in Shaping Muslim Character According to Quraish Shihab - Oktaviani, Sri; Rhamadhan, Yasvina (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
This research aims to determine the importance of prayer and the values contained in it. This research uses a qualitative research method used to research the condition of natural objects, where the researcher is the key instrument, data collection techniques are carried out in a combined manner, data analysis is inductive, and the results of qualitative research emphasize meaning rather than generalization. With this type of research, or library research, Prayer is the base and foundation of religion; prayer is one of the most effective ways of approaching Allah. In prayer, there are many values contained and can shape the character of a Muslim, and these values are: 1) Prayer is a means of getting closer to Allah and soothing the soul; 2). Prayer builds a clean and orderly person. 3) Prayer creates patient character, so from here, the role of prayer is very important for Muslims. Apart from being a way to get closer to Allah, prayer is also a character builder because there are many values that can be learned there.